Pascal, ou le règne de la force - Lucie Lebreton (Noctua, 2025)
If Pascal is essentially present in common representations and in the studies devoted to him as a spiritual and religious author, rarely has a thinker given force such a place in his reading of reality. In his view, it is the ‘queen of the world’, and even the queen of queens, since it governs the formidable powers of custom and imagination. We show here that Pascal’s analyses of force go far beyond the political framework in which they are generally confined. Indeed, Pascal’s reign of force seems to constitute a philosophical – as well as a scientific – thesis on the nature of reality: we live in a physical world, in a world of bodies entirely governed by force and, although we find it hard to recognise, along with concupiscence it constitutes ‘the source of all our actions’. This study thus sets out to highlight what makes Pascal a great thinker on force, one who will inspire the most daring philosophers in their speculations.